The evapotranspiration of crop protected by windbreak - Campi P.; Palumbo A.D.; Mastrorilli M. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The mechanisms with which windbreaks modify the microclimatic components and the evapotranspiration have been studied through laboratory testing (wind-tunnel), observations in the field (in Australia and in USA) and crop models. The extrapolation of the results of these studies does not allow for the quantification of their effective benefit in crop water consumption. This study proposes modifications to the Penman-Monteith formula to allow for calculation of the water requirements of wheat and bean in the presence of windbreaks. The microclimatic data were recorded in an experimental field protected by a windbreak of Cupressus arizonica L., positioned in a perpendicular direction to the prevailing winds (N). These results were used to correct the reference evapotranspiration formula (ET0) and the crop coefficients (Kc). With these corrections, the action of windbreaks on ET and water consumption were simulated. The simulations highlighted that, during 2000, the reduction of ET near the windbreak was 115mm for wheat and 95mm for bean. Different heights of the windbreak were simulated on a 1ha bean plot to quantify the contribution to effective water savings. The simulation highlighted that 8m high barriers offered the maximum water savings, estimated by 36 per cent greater than consumption for an unprotected plot.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)